Error Correction Model (ECM) For Macroeconomic Factors And LQ45 Stock Price Index - Yohanes Andri Putranto B; Bernadette Robiani; Mukhlis; Siti Rohima (Jurnal Ekonomi, 2024)
This research aims to test the causal effects of the inflation rate empirically, the Rupiah exchange rate against the United States Dollar, and world crude oil prices on the LQ45 stock price index. In its testing, this research uses the Error Correction Model (ECM) and uses data every month from 2000 to 2022. The research results show that the inflation rate, exchange rate and world gold prices significantly affect the LQ45 stock price index. Furthermore, the inflation rate and exchange rate have a negative influence on the LQ45 index. Not optimal company growth due to high inflation and exchange rates will affect public market share demand, thereby reducing share prices. Then, world crude oil prices positively influenced the LQ45 index. These results support previous research findings that changes in world crude oil prices positively affect stock market prices in developing countries.